Analysis of Temperature Field of Involute Spur Gear based on Friction Influence - Li Baoliang; Bi Lin; Tao Xuejuan (Jixie chuandong)
Taking apair of involute spur gear as the object of study,by using the formula of the friction coefficient obtained from the prophase study and the multi-bodied dynamics software ADAMS,it is possible to calculate the heat flow of friction at any point on the line of contact of driving gear and follower gear.The influence of rotate speed on gear temperature field is studied,by applying the ANSYS,the analysis of the steady temperature field of gear is carried out.The result shows that,in considering the friction coefficient of gears is changeable in different position of meshing,the analysis of gear temperature field distribution can be more accurate.The temperature field distribution on gear surface is related to the heat flow transmitted to gear surface and heat loss.The gear rotate speed is an important factor to influence gear temperature,the maximum temperature of the driving gear and the follower gear are directly proportional to the rotate speed.